The Effect of Knowledge and Patient Satisfaction on Interest in Online Reservations in the Outpatient Unit of Jember Clinic Hospital - Nurul Hamizah; Ratna Wardani; Novita Ana Anggraini (KHD Production, 2025)
Patient knowledge and satisfaction are important factors influencing interest in using healthcare services, including online reservation systems. Optimal use of information technology and appropriate patient education can improve the hospital service experience. This study aims to determine the influence of patient knowledge and satisfaction on their interest in using the online reservation system at the Outpatient Unit of Jember Clinic Hospital. This study used an analytical approach with a descriptive cross-sectional design. A sample of 100 respondents was determined using the purposive sampling technique based on the Slovin formula. Data analysis was performed using multiple linear regression using SPSS for Windows software. The analysis showed that patient knowledge positively and significantly affected interest in using online reservations (t-count 5.623). Patient satisfaction also positively and significantly influences this interest (t-count 3.273). Patient knowledge and satisfaction have been shown to drive interest in using online reservation systems significantly. Therefore, it is recommended that hospitals develop educational programs and improve the quality of online reservation services to increase patient interest.